Anterior versus posterior approach in the management of AO Type B1 & B2 traumatic thoracolumbar fractures: A level 1 trauma centre study. (February 2020) - Tan, Terence; Huang, Milly S.; Mathew, Joseph; Fitzgerald, Mark; Chan, Patrick; Hunn, Martin K.; Tee, Jin
Highlights: First study on surgical approaches in flexion-distraction thoracolumbar fractures. Ideal approach in AO Type B1/B2 thoracolumbar fractures is controversial. At 6 months, there is a trend toward improvement in ≥1 AIS grade in posterior group. Posterior approach resulted in better Cobb angle correction at follow up. Results to be interpreted with caution due to inherent selection bias in study. Abstract: The authors perform a retrospective trauma registry study to compare clinical, surgical and radiographical variables between anterior and posterior approaches in the management of AO Type B1 and B2 traumatic thoracolumbar fractures. Consecutive patients with surgically-managed AO Type B1 and B2 thoracolumbar fractures were included. Baseline demographics, surgical outcomes (including duration of surgery, postoperative morbidity etc.), neurological outcomes and radiographical outcomes (Cobb angle, Gardner angle) were compared between the anterior and posterior approaches. A total of 108 patients (anterior: n = 25, posterior: n = 83) were included. There were no significant between-group differences in baseline demographics and co-morbidities. Duration of surgery was longer in the anterior compared to posterior group (251 ± 91 min vs. 175 ± 69 min respectively, p < 0.00003). At six-months post-surgery, there was a trend towards improvement of at least one AIS grade in the posterior compared to the anterior group (85.7% vs. 33.3% respectively, p = 0.08). Postoperative complication profile showed no difference between approaches. The posterior approach resulted in better sagittal correction (Cobb angle; anterior: +1.05 ± 8.61 deg, posterior: −3.87 ± 9.88 deg, p = 0.03) and smaller loss of correction at 6-months post-surgery (Cobb angle; anterior: 8.36 ± 9.47 deg, posterior: 4.88 ± 6.62 deg, p = 0.048). This is the first study investigating surgical approach in flexion-distraction thoracolumbar fractures. Besides a shorter operative duration, the posterior approach seems to portend more favourable radiological correction at 6 months when compared to the anterior approach. Given the inherent selection bias of this study, definitive recommendations regarding the anterior versus posterior approach cannot be made. Further well-defined, prospective studies are necessary.